SUBTITUSI PENGGUNAAN SILASE TEBON JAGUNG DENGAN SILASE SORGHUM TERHADAP KECERNAAN SERAT KASAR DAN PROTEIN KASAR PADA SAPI LOKAL PENGGEMUKAN - Rizky Ramadhanu Wibisono, Liman, Farida Fathul, dan Erwanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2020)
The research that aimed to find out the level of substitution of corn crop silage with sorghum silage as a future feed ingredient on the fiber and protein digestibility of beef cattle has been held in May – July 2018 in the people's farm in Negla Sari village, South Lampung Regency, Lampung. This study used Completely Randomized Design with three treatments and three replications. The treatments given were R1: 30% corn crop silage + 70% concentrate; R2: 15% corn crop silage + 15% sorghum silage + 70% concentrate; and R3: 30% sorghum silage + 70% concentrate. This research used nine beef cattle which were allocated in individual cages. The data obtained were analyzed by analysis of covariance using a 5% significance level. Variables in this study were fiber and protein digestibility. The results showed that substitution of the use of corn crop silage with sorghum silage did not significantly affect (P>0.05) on the fiber and protein digestibility. Keywords: Beef cattle, Digestibility fiber, Digestibility protein, Sorghum silage, Silage corn, crop